Preservation of Early Cambrian animals of the Chengjiang biota - Gabbott, SE; Hou, X; Norry, M; Siveter, D (2004)
The Chengjiang biota of Yunnan, China, documents the earliest extensive radiation of the Metazoa recorded in the fossil record. Gauging preservational bias is crucial in providing an assessment of the completeness of this biota and thereby elucidating whether it represents a comprehensive depiction of Early Cambrian life. We here present a model to explain the nature of the exceptional preservation of the Chengjiang biota and details of the decay process. This study indicates that Chengjiang fossils were preserved through two taphonomic pathways that may have captured tissues of distinct compositions, and this finding should provide a foundation for the interpretation of Chengjiang fossils. Many Chengjiang fossils are preserved by pyrite (later pseudomorphed by iron oxides); the clay-rich host sediment was deficient in organic carbon but replete in available Fe, and this composition ensured that a decaying carcass acted as a local substrate for Fe- and S-reducing bacteria. Pyrite morphology probably reflects contrasts in the decay rate, and hence the H2S production rate, of different tissues in a carcass. Reactive, rapidly decaying tissues would have quickly supplied H2S, producing many pyrite nuclei, resulting in framboidal habits. More recalcitrant tissues would have produced H2S more slowly, so that crystal growth operated on fewer nuclei, resulting in larger euhedral pyrite crystals. Reflective films, especially common on Chengjiang arthropods, represent the remains of degraded carbon. © 2004 Geological Society of America.